Analisis Tingkat Kenyamanan Pejalan Kaki Terhadap Pemanfaatan Trotoar di Kawasan Alun-Alun Kota Batu - Zogara , Jumi Yantri U.; Rahma, Pamela Dinar; Yurnalisdel, Yurnalisdel (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
Batu City is a city that is the center and has a variety of supporting activities that make the Batu City Square area a place with 24-hour activities. This is because the Batu City square offers facilities that make visitors feel satisfied while in the square, the activities that occur in Batu city not only occur inside the building, but many activities that occur outside the building such as street vendors who carry out trading activities along the sidewalks of the Batu City Square Area. So that the real impact of the misuse of sidewalks by these street vendors causes pedestrians to use the shoulder of the road in the traffic area, this results in traffic flow becoming obstructed and less comfortable, causing the level of safety and comfort of road users to decrease. So it is necessary to analyze the level of service related to pedestrian satisfaction or comfort with the use of the Batu City Square sidewalk. The conclusions that can be drawn include the level of Service (LOS) of the Batu Square Area on the sidewalk with service level f. This level of service is quite good according to the minimum standard of sidewalk planning. The effective width of the existing sidewalk is not sufficient to accommodate the volume and flow of pedestrians in the Batu Square area, so that pedestrians are not free to precede other pedestrians or change the speed of walking.